2007
DOI: 10.1111/j.1600-6143.2006.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Adiponectin and Inflammation as Predictors of New-Onset Diabetes Mellitus After Kidney Transplantation

Abstract: The high incidence of new-onset diabetes mellitus after transplantation (NODAT) suggests the need to find new factors to explain the pathogenesis. Our objectives were (1) to confirm that low levels of pretransplant adiponectin are an independent risk factor for the development of NODAT in a larger transplanted population; (2) to analyze whether adiponectin is a better predictor of NODAT than other inflammatory markers (C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-a ) and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 32 publications
3
47
2
2
Order By: Relevance
“…Previous studies have shown that higher ADPN levels are protective against hypertension and new-onset diabetes after transplantation (18,19). We cannot comment on incident diabetes or the BP evolution in our study population; however, our study did not find any suggestion of improved overall patient outcome in those in the highest ADPN range.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have shown that higher ADPN levels are protective against hypertension and new-onset diabetes after transplantation (18,19). We cannot comment on incident diabetes or the BP evolution in our study population; however, our study did not find any suggestion of improved overall patient outcome in those in the highest ADPN range.…”
Section: Discussioncontrasting
confidence: 67%
“…HCV infection is a well known risk factor for not only NODAT, but also type 2 diabetes, probably due to impaired insulin action in the liver [35]. In addition to these risk factors, lower adiponectin and higher high sensitive Creactive protein (hs-CRP) levels were recently reported to be associated with NODAT [36], but we failed to observe such correlations.…”
Section: Discussioncontrasting
confidence: 54%
“…Recently, a possible relationship between low adiponectin levels and pancreatic ␤ cell dysfunction was suggested (3,4). A negative correlation between body mass index (BMI) and adiponectin levels has been established both in the general population and in patients with renal disease (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Recently, low pretransplantation adiponectin levels were shown to be associated with increased risk for posttransplantation diabetes mellitus (PTDM) (7).…”
mentioning
confidence: 99%